ANALISIS NILAI TAMBAH PRODUKSI ABON DAN TEPUNG IKAN LELE DENGAN PRINSIP ZERO WASTE ATAU NIR LIMBAH - Nurhayati, Immas; Suharti, Titing; Suartika, Ika (inovator, 2019)
The main purpose of this research is to analyze the economic value added of shredded and catfish flour production based on zero waste principle in Sekarwangi village, Sukabumi. The data used in this study are primary data where data is obtained directly from responden that is collected through interviews. This research was conducted for approximately two months. The process of changing from catfish to other products in the form of shredded and catfish flour gives added value both economically and to the benefit of environmental sustainability. The results of data processing show that processing raw material for unproductive catfish into shredded and catfish flour can provide economic value added Rp 19,500 for shredded from every 3 kg of catfish and 30,000 for catfish flour from every 5 kg of catfish bones. The application of zero waste technology in the production of shredded and catfish flour is to utilize all parts of catfish without any waste. The principle of zero waste is an environmentally friendly activity.